PENGARUH EDUKASI 7 LANGKAH CTPS MELALUI VIDEO ANIMASI TERHADAP TINGKAT PENGETAHUAN DAN TINDAKANDALAM UPAYA PENCEGAHAN PENYAKIT MENULARCOVID 19 KELAS 3 DI SDN TAPIR - Zulfia, Annisa Ayu; Lundy, Fiashriel; Lala, Handy (Poltekkes Kemenkes Malang, 2022)
Hands is one of the pathways of disease transmission, so washing hands with soap is the most effective way to kill viruses or bacteria. The purpose of this study is to determine the influence of animated video media on the level of knowledge and action about CTPS before and after being given education in an effort to prevent the COVID 19 disease. The population in this study was 28 grade 3 students, the sample used in this study was grade 3 students who totaled 26 respondents. The sampling technique uses total sampling. Data collection using questionnaires and observation sheets, data analysis using the Wilcoxon test. Wilcoxon's test results showed there was an effect of increasing knowledge and action where p value same with 0.000 less than a 0.005. This shows that the use of animated video media can increase the knowledge and actions of grade 3 students at SDN Tapir. This shows that the use of animated video media can increase the knowledge and actions of grade 3 students at SDN Tapir.The recommendation is that animated videos can be used to improve students CTPS actions as an effort in disease prevention.